Efeito da suplementação materna com palmitato de retinila sobre a concentração de retinol no colostro em condições de jejum e pós-prandial. - Cunha, Lahyana Rafaella de Freitas (2010)
Vitamin A is important in many essential body processes and its deficiency results in serious consequences for human health. Breast milk is the only source of this vitamin for children that are exclusively breastfed. Analysis of vitamin A in mother s milk is important because its concentration is related to maternal vitamin A status and to its ingestion by the mother during pregnancy. The aim of the present study was to assess the effect of maternal supplementation with retynil palmitate on the concentration of colostrum retinol under fasting and postprandial conditions. A total of 149 nursing mothers were recruited at the Januário Cicco Maternity School (Natal, Brazil) and allocated to two groups: Comparison (n = 69) and Test (n = 80). Blood and colostrum (in fasting and postprandial conditions) samples were collected up to 24hs after delivery. Serum retinol and colostrum levels were analyzed by high-performance liquid chromatography. The serum retinol level of 41.6 ± 12.7μg/dL (mean ± standard deviation) indicates adequate biochemical nutritional status. Colostrum retinol level was not influenced by serum retinol levels under any of the conditions established. In the colostrum, the retinol concentration in the unsupplemented test group was 67.3 ± 37.7 μg/dL under fasting and 80.3 ± 35.1 μg/dL under postprandial conditions (p<0.05), showing an increase of 19.3%. In the supplemented test group the values were 102.6 ± 57.3 μg/dL and 133.4 ± 78.3 μg/dL under fasting and postprandial, respectively (p<0.05), representing an increase of 30%. Considering that under fasting conditions most of the vitamin A transported to the milk originates in the retinol binding protein (RBP), the postprandial increase in colostrum retinol suggests a different transport mechanism of retinol to maternal milk from that performed by RBP. This situation becomes more evident under supplementation conditions.